Evaluation of the intensity and discomfort of perioperative thirst - Isadora Pierotti; Isabela Fernanda Larios Fracarolli; Lígia Fahl Fonseca; Patrícia Aroni (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To evaluate the intensity and discomfort of perioperative thirst and related factors during anesthesia recovery. Method: This is a quantitative, cross-sectional, descriptive study. Results: Of the 203 participants, 182 (89.6%) reported they were thirsty. The mean intensity of thirst was 6.9 measured using a verbal numerical scale of 0 to 10 and discomfort was 7.3 on a scale of 0 to 14. All attributes evaluated by the scale were cited including dry mouth and desire to drink water (87.3%), dry lips (79.1%), thick tongue feeling (43.4%), thick saliva (56.5%), dry throat (75.2%) and bad taste in the mouth (63.1%). There was a positive correlation between the intensity of thirst and discomfort assessed by the scale (Spearman coefficient: 0.474; p-value: <0.05). No correlation was found between age, length of fasting and use of opioids with the intensity of thirst and discomfort. Conclusion and implication in the clinical practice: Discomfort arising from the attributes of thirst is evidenced as the intensity of thirst increases.